The Assessment of Daylight and Glare in Classrooms Using Dynamic Indicators; the Case of SBU Faculty of Architecture and Urban Planning - Mohammad Ali Fadaii Ardestani; Haydar Nasseri Mobaaraki; Mohammad Reza Ayatollahi; Zahra Sadat Zomorrodian (صفه)
It demands reflections how to appropriately use daylight considering energy consumption, functions, and students’ and teachers’ performance in educational buildings. An inconsiderate design for windows, shadings and their accessories can result in glare and increased heating loads due to excessive direct sunlight reception or reduced daylight. Having daylight reception and glare control in mind, the present paper studies daylight, glare, and the effects of shading design on visual comfort using on-spot measurements and simulation for classrooms in the Faculty of Architecture and Urban Planning, Shahid Beheshti University. Both static and dynamic indicators have been employed here. The aim is to compare visual comfort conditions in different classes in order to choose suitable indicators. According to results among the studied indices, UDI 300-300(50%) and SVD are more appropriate for daylight and glare evaluations in the design process respectively.  The results also show that northeast facing classrooms enjoy the best visual comfort conditions. Moreover, south facing classrooms require moveable shading devices to receive suitable daylight and avoid glare. Meanwhile, the use of fix shading devices to reduce glare is unjustified as they significantly reduce daylight intake.